Potential-Scanning Sensing for Refractive Index Using an Indium Tin Oxide (ITO)-Coated Long-Period Fiber Grating (LPFG). (4th March 2022) - Okazaki, Takuya; Orii, Tatsuya; Tan, Shin-Yinn; Watanabe, Tomoaki; Taguchi, Akira; Rahman, Faidz A.; Kuramitz, Hideki
Abstract: Here is presented a potential-scanning sensing technique for refractive index detection using a long-period fiber grating (LPFG) coated with indium tin oxide (ITO). The LPFG was produced by an electric arc-induced technique. The sensing is achieved by controlling the electron density of the ITO electrode by potential scanning. The attenuation peak of the LPFG in the transmittance spectra is shifted by the application of a potential. Therefore, a transmittance–potential spectrum with an attenuation peak is obtained during potential scanning, and the refractive index near the sensor can be determined from the peak potential at attenuation. The ITO-LPFG was successfully employed to experimentally perform potential-scanning for refractive index detection in sucrose solutions with concentrations between 0% and 33%. A sensor resolution of 0.0063 ΔRI and a sensitivity of 9.9 V/RIU were obtained using this approach. These values were improved using wavelengths that were experimentally shown to provide high sensitivity and refractive index linearity. A minimum sensor resolution of 0.0017 ΔRI and a maximum sensitivity of 26.7 V/RIU were obtained at 1136 nm. The measurements determined from the peak potential in this work were unaffected by variations in the initial light intensity for individual samples. In addition, this sensing approach can be employed in the near-infrared region and is capable of real-time and remote monitoring.